Modulating T-cell activation with antisense oligoucleotides targeting lymphocyte cytosolic protein 2 - Iyer, Vaishnavi Srinivasan (2023)
Dysregulated T-cell activation is a hallmark of several autoimmune diseases such as rheumatoid arthritis (RA) and multiple sclerosis (MS). The lymphocyte cytosolic protein 2 (LCP2), also known as SLP-76, is essential for the development and activation of T cells. Despite the critical role of LCP2 in T-cell activation and the need for developing drugs that modify T-cell activation, no LCP2 inhibitors have been developed. This can be explained by the "undruggable" nature of LCP2, lacking a structure permissive to standard small molecule inhibitor modalities. Here, we explored an alternative drug modality, developing antisense oligonucleotides (ASOs) targeting LCP2 mRNAs, and evaluated its activity in modulating T-cell activation. We identified a set of 3' UTR targeting LCP2 ASOs, which knocked down LCP2 in a human T-cell line and primary human T cells and found that these suppressed T-cell receptor mediated activation. We also found that the ASOs suppressed FcεR1-mediated mast cell activation, in line with the role of LCP2 in mast cells. Taken together, our data provide examples of how immunomodulatory ASOs that interfere with undruggable targets can be developed and propose that such drug modalities can be used to treat autoimmune diseases.